Transitivity Dynamics: The Representation of Resistance in the Discourse of Iranian Spokesperson Ebrahim Zolfaghari - Rai Bagus Triadi; Adam Muhammad Nur; Tri Pujiati (Journal of Linguistics and Social Studies, 2026)
The conflict dynamics in the Middle East involving the United States, Israel, and Iran have generated extensive global controversy. Beyond triggering political and economic instability in various countries, this conflict has also evolved into a discursive arena characterized by competing narratives that attract international public attention. In this context, the President of the United States, Donald Trump, has frequently delivered statements via social media regarding the ongoing situation and his country’s stance in relation to Iran, often aimed at garnering global sympathy. Conversely, the Iranian spokesperson, Ebrahim Zolfaghari, has consistently responded to such statements, which are perceived as marginalizing Iran. Although conveyed in a predominantly informative tone, these responses implicitly construct Iran as a resilient and capable nation prepared to confront conflict. This study employs the framework of M. A. K. Halliday’s Systemic Functional Linguistics (SFL), with a particular focus on transitivity analysis to uncover the meanings realized within each clause of Zolfaghari’s discourse. The data consist of speech transcripts delivered by Zolfaghari, which are subsequently analyzed through clause-level segmentation. This analysis aims to identify the types of processes, participants, and circumstances employed in representing discourses of resistance, as well as to reveal how such linguistic constructions function as strategic tools of political communication within the context of international conflict.